2022
DOI: 10.3390/nu14020314
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Amounts of Common Ingredients Found in Energy Drinks and Shots

Abstract: Background: Energy drinks are one of the most popular packaged beverage products consumed within the United States (US). Energy drinks are considered a functional beverage, a category that also includes sports drinks and nutraceutical beverages. Purpose: The focus of the current study was to examine the nutrition fact panels of the top selling commercially available energy drink and energy shot products within the US to characterize common ingredient profiles to help establish a standard definition and ingredi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(50 citation statements)
references
References 42 publications
1
48
0
1
Order By: Relevance
“…Taurine is widely distributed in various tissues and organs, especially in excitable tissues, where the content is more abundant, such as the brain, heart and skeletal muscle ( De Luca et al, 2015 , Kp and Martin, 2022 , Schuller-Levis and Park, 2003 ).As a naturally occurring amino acid, taurine has few side effects, and current studies have not found any genotoxic, carcinogenic, or teratogenic effects ( Ripps & Shen, 2012 ). Due to its good safety, taurine is widely used in functional drinks ( Jagim et al, 2022 ), infant formula ( Almeida et al, 2021 ) and other products. Meat, especially seafood products, are rich in taurine ( Mendivil, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Taurine is widely distributed in various tissues and organs, especially in excitable tissues, where the content is more abundant, such as the brain, heart and skeletal muscle ( De Luca et al, 2015 , Kp and Martin, 2022 , Schuller-Levis and Park, 2003 ).As a naturally occurring amino acid, taurine has few side effects, and current studies have not found any genotoxic, carcinogenic, or teratogenic effects ( Ripps & Shen, 2012 ). Due to its good safety, taurine is widely used in functional drinks ( Jagim et al, 2022 ), infant formula ( Almeida et al, 2021 ) and other products. Meat, especially seafood products, are rich in taurine ( Mendivil, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…was 174.4 ± 81.1 mg (22). The declarations of several analyzed EDs do not state the levels of QUIN, SA, and BZA.…”
Section: Discussionmentioning
confidence: 88%
“…3 A recent study evaluated ingredients in the top 75 commercially available energy drinks and shots. 5 This study found that 67% of the energy drinks contained cobalamin at an average amount of 5,244% of the recommended daily value (DV), with a maximum of 41,667% DV in one energy shot. 5 The brand of energy drink consumed by our patient ranges in cobalamin content from 100% DV to 450% DV by flavor.…”
Section: Discussionmentioning
confidence: 95%
“…Foods naturally containing cobalamin have not been associated with contact dermatitis due to relatively low cobalt content 3 . A recent study evaluated ingredients in the top 75 commercially available energy drinks and shots 5 . This study found that 67% of the energy drinks contained cobalamin at an average amount of 5,244% of the recommended daily value (DV), with a maximum of 41,667% DV in one energy shot 5 .…”
Section: Discussionmentioning
confidence: 99%